How Important Are Choice, Autonomy, and Relationships in Predicting the Quality of Life of Nursing Home Residents?. (December 2021) - McCabe, Marita; Byers, Jessica; Busija, Lucy; Mellor, David; Bennett, Michelle; Beattie, Elizabeth
Older people face major challenges when they move into nursing homes, particularly in relation to independence and their ability to influence their activities of daily living (ADLs). This study evaluated the contribution of resident choice, as well as the staff–resident relationship, to promoting resident quality of life (QoL). A total of 604 residents from 33 nursing homes in Australia completed measures of QoL, perceived levels of choice in various ADLs, and the staff–resident relationship. A hierarchical regression demonstrated that the predictor variables accounted for 25% of the variance in QoL. Two of the four predictor variables (resident choice over socializing and the staff–resident relationship) significantly contributed to resident QoL. These findings reinforce the important contribution of autonomy and social relationships to resident QoL. Nursing home staff have a key role to play in supporting resident autonomy as a means of building residents' chosen social connections, and thereby promoting QoL.